Long‐term survival after treatment of idiopathic lung lobe torsion in 80 cases. Issue 4 (14th March 2020) - Rossanese, Matteo; Wustefeld‐Janssens, Brandan; Price, Cleo; Mielke, Ben; Wood, Sam; Kulendra, Nicola; Chanoit, Guillaume
Abstract: Objective: To report outcomes of dogs treated for lung lobe torsion (LLT) and to determine prognostic factors for survival. Study design: Retrospective multicenter study from four veterinary teaching hospitals. Animals: Dogs (n = 80) with LLT. Methods: Medical records were reviewed for clinical and histopathological findings. Long‐term outcome was assessed with an owner questionnaire. Lung lobe torsion was classified as idiopathic or secondary on the basis of the etiology. Results: The most represented breeds were pugs (47.5%) and sighthounds (16.2%). The cause of the LLT was considered primary in 77%, secondary in 21%, and unknown in 2% of dogs. Postoperative complications were recorded in 14% of dogs. Overall, 95% of dogs survived to discharge, and median follow‐up was 1095 days (range, 7‐3809). Owners assessed outcomes and quality of life as excellent in 93% and 89% of dogs, respectively. Primary LLT was associated with a longer survival (median not reached in the study) compared with secondary LLT (921 days; range, 7‐2073; P = .001). Conclusion: Overall long‐term survival after lung lobectomy for LLT was excellent. Primary LLT was associated with longer survival compared with secondary LLT. Long‐term owner evaluation of clinical outcome for dogs undergoing lung lobectomy for LLT was considered excellent. Clinical impact: Dogs with primary LLT undergoing lung lobectomy have a longer survival time compared with dogs with secondary LLT and have an excellent postoperative outcome.